Perancangan Aplikasi Raport Online Berbasis Web The Design Of Web-Based Applications Online Raport (Information Technology and Telematics, 2015)
ABSTRACTRaport is a result obtained by learning activities of students in school given each semester. That report contain academic values written in a book and there is no time efficiency in creatingraport process becomesone of the problem when the raport division implemented.The purpose of this reseach is designing raport online application that could processing and printing students valuesof each homeroom teacher. Designing raport online will ease students in seeing value and updating personal data  of  student.  System  development  methods  in  creating  personal  online  raport  appllication  i s  using  prototype methods, and for system designis usingUML(Unified Modelling Language). Software that used in this designing online applications are MySQL, PHP, and Xampp as local server.This research will produce online raport application which can be used by homeroom teacher to give values for each students in class. Also can be used by students to ssee values and update personal data for aech students.Keywords: Online Raport, Prototype, PHP, MySQL.